Analisis Kemampuan Regulasi Diri Dan Motivasi Belajar Mahasiswa Pada Masa Pembelajaran Daring - Ruli Meiliawati; Anggi Ristiyana Puspita Sari (FKIP Universitas Palangka Raya, 2021)
All universities that are forced to conduct online learning due to pandemic era greatly affects the interpersonal conditions of students. This changing also influences student’s performance quality. The paper presents a descriptive quantitative which aims to explore: 1) differences in self-regulated learning between cumlaude and non-cumlaude students, 2) differences in learning motivation between cumlaude and non-cumlaude students, 3) correlations of self-regulated learning, learning motivation, and achievement in cumlaude students, and 4) correlation of self-regulated learning, learning motivation, and achievement in non-cumlaude students. The data collection technique used a questionnaire technique with instruments in the form of a self-regulated learning and learning motivation questionnaire, both of which were adapted questionnaires. The data obtained were then analyzed using the free sample t test and correlation test using the SPSS program. The results obtained indicate that: 1) there are differences in self-regulated learning between cum laude and non-cum laude students, 2) there are differences in learning motivation between cum laude and non-cum laude students, 3) there is a correlation between self-regulated learning, learning motivation, and achievement in cum laude students, and 4) there is no correlation between self-regulated learning, learning motivation, and learning outcome in non-cumlaude students.